Developmental characteristics of the hypothalamo-hypophyseal-adrenal system in chronic heterotypical stress - Khlebnikov, Vladimir; Kuznetsov, S. L.; Chernov, D. A.; Agrytskov, A. M.; Ahmad, Arsalan; Mohamed Noor Khan, Nor-Ashikin; Ullah, Mohammad Fahad; Kapitonova, Marina Yu (Springer New York, 2016)
Experimental studies of the developmental characteristics of the adaptation of the hypothalamo-hypophyseal-adrenal system (HHAS) to the actions of heterotypical stressors in the context of stress-associated behavioral reactions were studied. Sprague–Dawley rats aged three (young), six (adult), and 12 (aged) months (total number of animals = 36) were exposed to changing stressors for seven days, after which their behavioral reactions were assessed. Histological changes in the hypothalamus, hypophysis, and adrenals were studied and compared with age-matched controls, and immunochemical reactions to corticoliberin (CRF), adrenocorticotropic hormone (ACTH), ED1, PCNA, and caspase-3 were performed, with subsequent image analysis. In aged animals, as compared with young and adult animals, the levels of activation of the components of the HHAS provided evidence of dissociation in its central component and blockade of the adaptive desensitization typical of young and adult animals. In particular, aged animals showed a high level of CRF expression in the hypothalamus in stress, with a relatively low level of ACTH expression in the adenohypophysis and a high level of adrenal activity. Decreases in HHAS plasticity in aged rats as compared with other age groups corresponded to behavioral changes seen in these animals, demonstrating decreases in the ability of aged animals to adapt to chronic exposure to unpredictably changing stressors.